2006
DOI: 10.1007/s10803-006-0318-4
|View full text |Cite
|
Sign up to set email alerts
|

Treating Anxiety Disorders in Children with High Functioning Autism Spectrum Disorders: A Controlled Trial

Abstract: A family-based, cognitive behavioural treatment for anxiety in 47 children with comorbid anxiety disorders and High Functioning Autism Spectrum Disorder (HFA) was evaluated. Treatment involved 12 weekly group sessions and was compared with a waiting list condition. Changes between pre- and post-treatment were examined using clinical interviews as well as child-, parent- and teacher-report measures. Following treatment, 71.4% of the treated participants no longer fulfilled diagnostic criteria for an anxiety dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
316
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 349 publications
(332 citation statements)
references
References 85 publications
13
316
2
1
Order By: Relevance
“…CBT for anxiety was not significantly different from control conditions as reported by the children (random effects model ES = 0.68 (95% CI, 20.17 to 1.54; z = 1.56, P = .12; fixed effect model ES = 0.48). Furthermore, this effect appears to be largely driven by 1 study, 35 with an ES of 2.69 (ESs in other studies ranges from 0.03 to 0.49). We performed a sensitivity analysis by removing the Chalfant et al study and found that the estimated weighted mean ES decreased from 0.68. to 0.17 (95% CI, 20.13 to 0.47; z = 1.09, P = .27).…”
Section: Child-reported Anxietymentioning
confidence: 79%
See 4 more Smart Citations
“…CBT for anxiety was not significantly different from control conditions as reported by the children (random effects model ES = 0.68 (95% CI, 20.17 to 1.54; z = 1.56, P = .12; fixed effect model ES = 0.48). Furthermore, this effect appears to be largely driven by 1 study, 35 with an ES of 2.69 (ESs in other studies ranges from 0.03 to 0.49). We performed a sensitivity analysis by removing the Chalfant et al study and found that the estimated weighted mean ES decreased from 0.68. to 0.17 (95% CI, 20.13 to 0.47; z = 1.09, P = .27).…”
Section: Child-reported Anxietymentioning
confidence: 79%
“…34,35,39,40,42,43 As shown in Fig 2, CBT was superior to control conditions for anxiety symptoms in children with ASD as reported by the parents (random effects model ES = 1.19; 95% CI, 0.23 to 2.14; z = 2.44, P = .02; fixed effect model ES = 0.78). However, one study 35 had an ES estimate (d = 4.34) that was much larger than that of the other studies (range, d = 0.10-1.23). We explored this effect by conducting a sensitivity analysis by removing the outlier, and we found that the estimated weighted mean ES would decrease from 1.19 to 0.57 (95% CI, 0.16 to 0.97; z = 2.73, P = .006) with the Chalfant et al study removed.…”
Section: Parent-rated Anxietymentioning
confidence: 86%
See 3 more Smart Citations